Geolocators link marine mercury with levels in wild seabirds throughout their annual cycle: Consequences for trans-ecosystem biotransport. (1st September 2021) - Shoji, Akiko; Elliott, Kyle H.; Watanuki, Yutaka; Basu, Niladri; Whelan, Shannon; Cunningham, Joshua; Hatch, Scott; Mizukawa, Hazuki; Nakayama, Shouta M.M.; Ikenaka, Yoshinori; Ishizuka, Mayumi; Aris-Brosou, Stéphane
Abstract: Seabirds are widely used as indicators of marine pollution, including mercury (Hg), because they track contaminant levels across space and time. However, many seabirds are migratory, and it is difficult to understand the timing and location of their Hg accumulation. Seabirds may obtain Hg thousands of kilometers away, during their non-breeding period, and deposit that Hg into their terrestrial breeding colonies. We predicted that Hg concentration in rectrices reflects exposure during the previous breeding season, in body feathers reflects non-breeding exposure, and in blood collected during breeding reflects exposure during current breeding. To test this hypothesis, we measured total Hg concentration in these three tissues, which reflect different timepoints during the annual cycle of rhinoceros auklets ( Cerorhinca monocerata ) breeding on both sides of the North Pacific (Middleton Island in Alaska and Teuri Island in Hokkaido), and tracked their wintering movement patterns with biologging devices. We (i) identify the wintering patterns of both populations, (ii) examine Hg levels in different tissues representing exposure at different time periods, (iii) test how environmental Hg exposure during the non-breeding season affects bird contamination, and (iv) assess whether variation in Hg levels during the non-breeding season influences levels accumulated in terrestrial plants. Individuals from both populations followed a figure-eight looping migration pattern. We confirm the existence of a pathway from environmental Hg to plant roots via avian tissues, as Hg concentrations were higher in plants within the auklet colonies than at control sites. Hg concentrations of breast feathers were higher in Alaskan than in Japanese auklets, but Hg concentrations in rectrices and blood were similar. Moreover, we found evidence that tissues with different turnover rates could record local anthropogenic Hg emission rates of areas visited during winter. In conclusion, Hg was transported across thousands of kilometers by seabirds and transferred to local plants. Graphical abstract: Image 1 Highlights: Geographical variation of Hg across the Pacific Ocean was measured in seabirds, and the impact of trans-ecosystem biotransport was quantified. Levels of mercury in auklet feathers at both sites of Pacific were within reported values, but above thresholds for adverse effects. Hg concentrations in seabird tissues were correlated with environmental Hg concentrations. Seabirds transported mercury across long distances and transferred it to terrestrial plants. Feather samples are useful indicators of mercury at sea. Abstract : CAPSULE: Tracing ocean-wide Hg levels to seabird tissues to terrestrial plants across the North Pacific provides a mechanistic link for trans-ecosystem Hg transfer.